Legal Awareness and National Resilience in The Socio-Cultural Field - Anang Puji Utama (Faculty of Social Science, Universitas Negeri Malang, 2023)
The role of law as a regulator that can be a means of community control is a strategic tool in building national resilience. However, the law also requires obedience from the community as a departure from legal awareness. The norms in the law will only be norms without obedience from the community. This research is conducted using normative legal research methods, namely research by analyzing laws and regulations that apply or are applied to a particular legal problem. This paper aims to examine the relationship between law and national resilience in the socio-cultural field and examine efforts to improve national resilience through building public legal awareness in order to achieve a high level of legal obedience. The method is done through a literature study. The findings of this paper are the link between national resilience with awareness and obedience to the law needed for the smooth implementation of national development. The rule of law, as the nature of other rules, requires public obedience to obey or behave in accordance with the values in the law. This obedience requires legal awareness from the community. Legal awareness, public obedience, and national resilience in social aspects have a relationship with each other. High legal awareness will enable one to realize the level of obedience to the law that will strengthen national resilience.